The search for cathelicidins in Gasterosteus aculeatus - Guðrún Ýr Ásgeirsdóttir 1984- (2010)
Cathelicidins are antimicrobial peptides that have been found in many diverse mammals as well as in fish and chicken. The fact that it can be found in different classes of animals indicates that this gene is important for organism so that it will be selected for. Recent studies have shown that cathelicidin in mammals is at the front line in defending its host to microbe invasions. Its role in fish has not been well established, though studies on cathelicidin in rainbow trout, Atlantic salmon and Atlantic cod strongly indicate that cathelicidin has a role in innate immunity for fish and is well conserved between species. The aim of this project was to discover a cathelicidin gene in the stickleback species (G.aculeatus). The presence of cathelicidin had been indicated by a previous study, and if cathelicidin was found a further aim was to isolate that gene for further studies. This did not prove possible, since a successful detection was not achieved. It is quite likely that the previous study was tainted with salmon cDNA, which would give a false positive for stickleback cathelicidin gene. Also, both reference samples (cod and salmon) were infected with bacteria, but infection of an organism provides increased amounts of cathelicidin. This was not done for the stickleback and therefore might have given a false negative, compared to the cod and salmon signal. In conclusion the methods used in this study, did not prove to be powerful enough to detect and isolate the gene.